ESAT-6 Inhibits Production of IFN-γ by Mycobacterium tuberculosis-Responsive Human T Cells() - Wang, Xisheng (J Immunol, 2009)
The Mycobacterium tuberculosis early secreted Ag of 6 kDa (ESAT-6) is a potent Ag for human T cells and is a putative vaccine candidate. However, ESAT-6 also contributes to virulence in animal models, mediates cellular cytolysis, and inhibits IL-12 production by mononuclear phagocytes. We evaluated the effects of ESAT-6 and its molecular chaperone, culture filtrate protein of 10 kDa (CFP10), on the capacity of human T cells to produce IFN-γ and proliferate in response to TCR activation. Recombinant ESAT-6, but not CFP10, markedly inhibited IFN-γ production by T cells stimulated with M. tuberculosis or with the combination of anti-CD3 and anti-CD28, in a dose-dependent manner. ESAT-6 also inhibited T cell production of IL-17 and TNF-α but not IL-2. Preincubation of ESAT-6 with CFP10 under conditions that favor dimer formation did not affect inhibition of IFN-γ. ESAT-6 decreased IFN-γ transcription and reduced expression of the transcription factors, ATF-2 and c-Jun, which normally bind to the IFN-γ proximal promoter and stimulate mRNA expression. ESAT-6 inhibited T cell IFN-γ secretion through mechanisms that did not involve cellular cytotoxicity or apoptosis. ESAT-6, but not CFP10, bound to T cells and inhibited expression of early activation markers without reducing activation of ZAP70. We conclude that ESAT-6 directly inhibits human T cell responses to mycobacterial Ags by affecting TCR signaling pathways downstream of ZAP70.